73.6k views
5 votes
Solve the linear system
Eq 1: 2x -4y = -2, Eq 2: 3x + y =4

User Ben Quan
by
5.1k points

1 Answer

3 votes

Answer:

(1, 1 )

Explanation:

Given the 2 equations

2x - 4y = - 2 → (1)

3x + y = 4 → (2)

Multiplying (2) by 4 and adding the result to (1) will eliminate the y- term

12x + 4y = 16 → (3)

Add (1) and (3) term by term to eliminate y

14x + 0 = 14

14x = 14 ( divide both sides by 14 )

x = 1

Substitute x = 1 into either of the 2 equations and solve for y

Substituting into (2)

3(1) + y = 4

3 + y = 4 ( subtract 3 from both sides )

y = 1

solution is (1, 1 )

User Alex Nelson
by
5.4k points